Project ASTRAL: All-sky Space Telescope to Record Afterglow Locations - Tsarevsky, G.; Bisnovaty-Kogan, G.; Pozanenko, A.; Beskin, G.; Popov, G.; Rumyantsev, V. (Известия Крымской астрофизической обсерватории, 2016)
ASTRAL is a project incorporating a wide-field optical telescopes on board of a small satellite dedicated to the whole-sky detection of a variety of rapid astronomical phenomena, particularly optical flashes associated with gamma ray bursts (GRB). Those flashes only visible optically (so called "orphans"), as well as those preceding associated GRBs, cannot be detected in the current triggering mode of the world wide GRB Coordinates Network (GCN). Hence ASTRAL would have a unique opportunity to trigger a follow-up multi-frequency study via GCN. ASTRAL consists of a set of 13 wide-field cameras (each with FOV = 70°) equipped with 4096x4096 CCDs. The detection method is based on the Digital Blink Comparator mode, with a template of a complete sample of ∼ 2 million stars down to 12m, precisely measured in the HIPPARCOS and TYCHO-2 missions. Supernovae, novae and nova-like explosions, fast variable AGNs, flare stars, and even new comets would be promptly detected as well. Monitoring of Near-Earth objects (NEO) is of special interest. Thus ASTRAL would also be an original working prototype of the prospective major space mission to monitor on-line all the sky - a high priority instrument of the 21st Century astrophysics.